Pengaruh Formula Coating terhadap Viabilitas dan Vigor serta Daya Simpan Benih Padi (Oryza sativa L.) - Tantri Palupi; Satriyas Ilyas; Muhammad Machmud; Eny Widajati (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2012)
The objectives of this research were to find the most compatible coating formula for rice seeds (Experiment 1), and to evaluate the effect of coating formula on viability, vigor and storability of the seeds (Experiment 2). This research was conducted in Laboratory of Seed Science and Technology at IPB, Bogor and Laboratory of Seed Technology at PT East West Seed Indonesia, Purwakarta from December 2010 to February 2011. In Experiment 1, the ten coating materials (formula) were arranged in single factor of Completely Randomized Design with four replications, i.e. uncoated seed, 3% alginate + 1% talc, 3% alginate + 1% gypsum, 3% alginate + 1% peat, 3% arabic gum + 1% talc, 3% arabic gum + 1% gypsum, 3% arabic gum + 1% peat, 1.5% CMC + 1% talc, 1.5% CMC + 1% gypsum, and 1.5% CMC + 1% peat. Experiment 2 used Split Plot Design with four replications. The main plot was storage periods i.e. 0, 1 and 2 months. The seeds were stored in two storage conditions: ambient and air conditioned room. The subplot was coating formula (same as in Experiment 1). The results of Experiment 1 showed that the most compatible coating material for rice seeds were 1.5% CMC + 1% talc, and 1.5% CMC + 1% gypsum, these formula were able to maintain vigor of the coated seeds. In Experiment 2, coating formula of 1.5% CMC + 1% peat generated higher seed vigor than uncoated seeds after two months storage, 3% gum arabic + 1% gypsum was able to keep vigor for one month storage in ambient condition. The coating formula of 3% alginate + 1% peat was able to keep viability and vigor of the coated seeds for two months in air conditioned room. Keywords: seed coating material, seed quality, seed storage condition, seed storability